Issue estoppel created by consent judgments: Dissonance between the principles underlying settlement and court decisions - QUEK ANDERSON, Dorcas (Institutional Knowledge at Singapore Management University, 2017)
This paper discusses theapplication of the concept of issue estoppel to consent judgments. Four HighCourt decisions have reached conflicting conclusions on this topic and createdconsiderable conceptual difficulties. The paper discusses the underlyingreasons for the differences in these decisions, focusing on the dissonancebrought about by the conventional policies underlying issue estoppel and the differingpolicy concerns applying to consent judgments. The paper recommends that thecourts take into account the unique nature of consent judgments, and use amodified test of issue estoppel for consent judgments. It also suggests thatthe extended doctrine of res judicatais much more appropriate for consent orders.